Impact of concerning excipients on animal safety: insights for veterinary pharmacotherapy and regulatory considerations - Thomazini, Vanessa Cola; da Cunha, Gabriel Mendes; Guimarães, Nayhara Madeira; Saleme, Soraya Dias; de Melo, Rita Cristina Gonçalves; de Paula, Geanne Aparecida [UNESP]; Carvalho, Suzana Gonçalves [UNESP]; Chorilli, Marlus [UNESP]; dos Santos Giuberti, Cristiane; Villanova, Janaina Cecília Oliveira (Springer Nature, 2024)
Objectives: Veterinarians and pharmacists are familiar with the efficacy and safety aspects attributed to active pharmaceutical ingredients included in medicines, but they are rarely concerned with the safety of excipients present in medicines. Although generally recognized as safe, excipients are not chemically inert and may produce adverse events in certain animal populations. This review aims to present excipients of concern to these populations and highlight their relevance for rational veterinary pharmacotherapy. Evidence acquisition: A comprehensive review of the literature about the existence of adverse reactions in animals caused by pharmaceutical excipients was carried out based on an exploratory study. An overview of the correct conditions of use and safety of these excipients has also been provided, with information about their function, the proportion in which they are included in the different pharmaceutical dosage forms and the usual routes of administration. Results: We identified 18 excipients considered of concern due to their potential to cause harm to the health of specific animal populations: bentonite, benzalkonium chloride, benzoic acid, benzyl alcohol, ethanol, lactose, mannitol, mineral oil, monosodium glutamate, polyethylene glycol, polysorbate, propylene glycol, sodium benzoate, sodium carboxymethylcellulose, sodium lauryl sulfate, sulfites, polyoxyethylene castor oil derivatives, and xylitol. Among the 135 manuscripts listed, only 24 referred to studies in which the substances were correctly evaluated as excipients. Conclusions: Based on the information presented in this review, the authors hope to draw the attention of professionals involved in veterinary pharmacotherapy to the existence of excipients of concern in medicines. This information contributes to rational veterinary pharmacotherapy and supports veterinary pharmacovigilance actions. We hope to shed light on the subject and encourage studies and new manuscripts that address the safety of pharmaceutical excipients to the animal population. Graphical Abstract: (Figure presented.)
Keywords: Adverse reaction; Animal safety; Excipient of concern; Veterinary pharmacotherapy